REDUCING EMPLOYEE TURNOVER INTENTION - Nazifah Husainah; Azimah Hanifah (Universitas Padjadjaran, 2021)
5 in recent years, employees of company earnings in foodhall in Jakarta fluctuations have relatively high. This condition is caused by problems about the intention of earnings, The organization, and the company. The purpose of study is to examine the effect of employee organizations and culture in earnings intention, both directly and indirectly through the organization to an enterprise in foodhall in Jakarta. This method uses a method descriptive and explanations at least 200 samples from the survey respondents from 25 outlets in Jakarta that foodhall. Structural Equation Model data verified by lisrel 8.80 modeling methods of using. The results show that cultures of organization a lively and have high impact significant directly to organizations commitment but has a negative and significant effect directly in circulation intention, commitment organization negative and had an impact a significant impact on earnings intention, the culture of organization negative and had an impact a significant impact on earnings intention through commitment organization. Organization culture and organization commitment simultaneously affect earnings intention. The commitment the organization has more the role of dominant in reducing the level of dropping in and out of employees intention and other based on the survey results was the partial organization mediation about the effects of an organization’s culture in circulation intention.